2018
DOI: 10.2147/copd.s158818
|View full text |Cite
|
Sign up to set email alerts
|

The link between chronic obstructive pulmonary disease phenotypes and histological subtypes of lung cancer: a case–control study

Abstract: BackgroundCOPD is considered an independent risk factor for lung cancer. COPD and lung cancer are both very heterogeneous diseases, and the study herein investigates the link between COPD phenotypes and specific histological subtypes of lung cancer.MethodsThis case–control study comprised 2,283 patients with newly diagnosed pathological lung cancer and 2,323 non-lung cancer controls. All participants underwent pulmonary function tests. The diagnosis of COPD was based on Global Initiative for Chronic Obstructiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 59 publications
0
11
0
1
Order By: Relevance
“…Patients with emphysematous lungs had a higher prevalence of male sex and a smoking history [12, 14]. Regarding histology, emphysema lung was associated with a risk of small cell lung carcinoma (SCLC) and squamous cell carcinoma [28, 29]. In the present study, male sex, thinner patients, higher smoking index, squamous cell carcinoma, high histologic grade, and pleural invasion-positive were more frequent in patients with emphysema, similar to previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with emphysematous lungs had a higher prevalence of male sex and a smoking history [12, 14]. Regarding histology, emphysema lung was associated with a risk of small cell lung carcinoma (SCLC) and squamous cell carcinoma [28, 29]. In the present study, male sex, thinner patients, higher smoking index, squamous cell carcinoma, high histologic grade, and pleural invasion-positive were more frequent in patients with emphysema, similar to previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…However, FZR1, but not MTA1 and PKMYT1, was validated to be Introduction Chronic obstructive pulmonary disease (COPD) and lung cancer are common causes of death worldwide. 1 Previous studies reported COPD was more likely to develop lung cancer than those with normal lung function, [2][3][4][5] indicating COPD is an independent risk factor for lung cancer, 3,[6][7][8] which may result in co-existing of COPD and lung cancer. In this process, genetic susceptibility is one of the welldescribed mechanisms for co-existing of COPD and lung cancer.…”
Section: What Is Added To This Topic?mentioning
confidence: 99%
“…In contrast, in a sample of 72 consecutive LC cases sourced from the Navarre University LC screening programme (Spain) with 3,477 participants, González et al (39) detected that risk of LC was associated with presence of airflow obstruction (OR =2.8; 95% CI, 1.6-5.2) and centrilobular emphysema (OR =34.3; 95% CI, 25.5-99.3), and that this risk decreased when associated with paraseptal emphysema (OR =4; 95% CI, 3.6-34.9). In a case-control study comprising 2,283 LC cases and 2,323 controls, with detection of COPD in 32.8% of patients in the LC group, Wang et al (40) found an association between risk and diagnosis of COPD (OR =2.88; 95% CI, 2.48-3.14), and in the case of the phenotype, between risk and presence of emphysema (OR =4.43; 95% CI, 2.85-6.88, P<0.001), after adjustment for smoking habit.…”
Section: Type Of Emphysema and Risk Of Lcmentioning
confidence: 99%